The Importance of Rapid Influenza Testing in Pediatric Primary Care: Experience During Three Consecutive Influenza Seasons (2016–2019) in Barcelona (Catalonia, Spain) - van Esso, Diego; Vilà, Monica; Andrés, Cristina; Iglesias, Sheila; Ferrer, Josep; Losada, Lucia; Ricos, Gemma; Sanchez, Lorena; Morera, Patricia; Pérez, Mar; Ferrandez, Mª Angeles; Hernando, Esther; et al. (Frontiers in Pediatrics, 2020)
Clinical diagnosis of influenza has low sensitivity in infants and children. Signs and symptoms are nonspecific and similar to those of other respiratory viruses. Rapid influenza diagnostic tests (RIDTs) with adequate sensitivity and specificity used at the point of care can be useful for an etiologic diagnosis of influenza in primary care. This should have an impact on better management of these patients. We conducted a study during three consecutive influenza seasons (2016-17, 2017-18, and 2018-19) in paediatric primary care settings collecting data from influenza point-of-care tests (POCTs)-confirmed ≤ 6year-old patients. The data from influenza POCT-confirmed patients (Group_1) were compared to patients with clinical diagnosis of influenza-like illness (ILI) (Group_2), or fever (2016 ICD-10 code R50) with no other signs of influenza (Group_3). Group_1patients had 0.19 (2016-17) and 0.23 (2017-18) additional visits compared to 0.48 (2016-17) and 0.49 (2017-18) p <0.001 for Group_2 and 1.01 (2016-17) and 0.80 (2017-18) p<0.001 Group_3 patients. Antibiotic prescription was lower in Group_1 (10.2%) vs Group_3 (17.2%) p<0.002, although the difference was statistically significant only in 2017-18 but not in 2016-17 season. During the last season (2018-19), POCTs results were transmitted in real time to the reference laboratory via the cloud, which allowed immediate monitoring of influenza viruses circulating in the community for surveillance purposes. In our experience, the use of POCTs has a great potential in primary care specially in infants and young children in which the diagnosis maybe missed due to nonspecific signs and symptoms.